(untitled) (Damascus University Journal of agriculture sciences, 2019)
This study was carried out in order to isolate and characterize Pediococcus bacteria from some Syrian foods and study the growth inhibitory effect of the isolated strains against of the bacteria Listeria monocytogenes. 119 isolates were isolated from different samples of local fermented food and defined based on the characteristics of lactic acid bacteria. The microscopic examinations show presence of 20 oval-shaped isolate Conducted by biochemical tests to determine which isolates follow the Pediococcus genus. The isolates were classified using PCR technique and the isolates were classified as API / 50CHL. The result shows that 8 isolates belong to P. acidilactici and 10 isolates belong P.pentosaceus and 2 isolates of P. damnosus. These isolates were investigated for their inhibitory effect against Listeria monocytogenes. All isolates have a potent inhibitory effect of L. monocytogenes. The results showed that isolates 16 and 12 have the largest inhibition zone of diameter 27mm.